Anticorrosive Behavior of Aluminum Nitride Surface Exposed to Chlorine Trifluoride Gas at High Temperatures. (8th March 2021) - Haruguchi, Miyu; Hayashi, Masaya; Irikura, Kenta; Habuka, Hitoshi; Takahashi, Yoshinao
Abstract : The powder and plate of aluminum nitride were exposed to chlorine trifluoride gas at the concentration of 100% and at atmospheric pressure for 10 min and temperatures up to about 1000 °C. With the increasing temperature, the weight of the aluminum nitride plate increased in the temperature range between 750 °C and 800 °C, while it decreased at temperatures higher than 800 °C. The thickness also increased at temperatures higher than 750 °C. The change in the aluminum nitride plate thickness showed a peak at 800 °C. The surface remained smooth at temperatures lower than 900 °C. However, the surface had small pits at 995 °C, because the aluminum trifluoride, produced by the chlorine trifluoride gas, was considered to slightly sublimate and affect the surface morphology. Overall, the aluminum nitride remained anticorrosive to the chlorine trifluoride gas at temperatures lower than 900 °C. When the aluminum nitride was used in the silicon carbide etching reactor, its surface was rather smooth after repetitive exposures to the chlorine trifluoride gas at 500 °C.